Groundwater flow induced collapse and flooding in Noctis Labyrinthus, Mars. (May 2016) - Rodriguez, J. Alexis P.; Zarroca, Mario; Linares, Rogelio; Gulick, Virginia; Weitz, Catherine M.; Yan, Jianguo; Fairén, Alberto G.; Miyamoto, Hideaki; Platz, Thomas; Baker, Victor; Kargel, Jeffrey; Glines, Natalie; et al.
Abstract: Catastrophic floods of enormous proportions played a major role in the excavation of some of the Solar System׳s largest channels, the circum-Chryse outflow channels. The generation of the floods has been attributed to both the evacuation of regional highland aquifers and ancient paleo-lakes. Numerous investigators indicate that these source regions were likely recharged and pressurized by eastward groundwater flow via conduits extending thousands of kilometers from an elevated groundwater table in the Tharsis volcanic rise. This hypothesis remains controversial, largely because subsequent stages of Valles Marineris development and enlargement would have resulted in the widespread destruction of the proposed groundwater pathways. Here, we show that Noctis Labyrinthus, a unique system of troughs connecting the Tharsis volcanic rise and western Valles Marineris, retains geologic evidence of conduit development associated with structurally-controlled groundwater flow through salt-rich upper crustal deposits. The inferred groundwater flow spatial pattern is in agreement with aquifer drainage from the Tharsis volcanic rise region. Our investigation indicates that subsequent surface collapse over these conduits during the Hesperian Period resulted in the generation of large basins in the central and eastern regions of Noctis Labyrinthus, and contributed to chasmata formation in the western portion of Valles Marineris. The lava-covered floors of these basins, dated by previous workers as Late Amazonian, contain hydrated mineral deposits coexisting spatially with decameter-scale features that we interpret to be lacustrine and periglacial in origin. The proposed paleo-lake sites also include chaotic terrains, which could comprise groundwater discharge zones, pointing to regional hydrologic processes that likely operated from the Early Hesperian until a few tens of millions of years ago. Episodic fluidized discharges from eastern Noctis Labyrinthus troughs delivered vast volumes of sediments and volatiles into western Valles Marineris, contributing to the construction of a regional volatile-rich stratigraphy. Intermittent formation of lakes within regional tectono-volcanic basins could have lasted hundreds of millions of years, thus, we highlight the potential of Noctis Labyrinthus as a region of prime interest for astrobiological exploration. Highlights: During hundreds of millions of years Noctis Labyrinthus episodically experienced volcanic and hydrologic resurfacing. Groundwater flow through regional upper crustal salt deposits formed conduits. The conduits might have been part of an ancient groundwater system extending to the head regions of the Chryse outflow channels. Collapse over the conduits produced enclosed basins, where lavas and lacustrine sediments accumulated. The floors of these basins might comprise outstanding astrobiological targets.